Isoflurane abolishes spontaneous firing of serotonin neurons and masks their pH/CO(2) chemosensitivity - Massey, Cory A. (J Neurophysiol, 2015)
Serotonin (5-hydroxytryptamine, 5-HT) neurons from the mouse and rat rostral medulla are stimulated by increased CO(2) when studied in culture or brain slices. However, the response of 5-HT neurons has been variable when animals are exposed to hypercapnia in vivo. Here we examined whether halogenated inhalational anesthetics, which activate TWIK-related acid-sensitive K(+) (TASK) channels, could mask an effect of CO(2) on 5-HT neurons. During in vivo plethysmography in mice, isoflurane (1%) markedly reduced the hypercapnic ventilatory response (HCVR) by 78–96% depending upon mouse strain and ambient temperature. In a perfused rat brain stem preparation, isoflurane (1%) reduced or silenced spontaneous firing of medullary 5-HT neurons in situ and abolished their responses to elevated perfusate Pco(2). In dissociated cell cultures, isoflurane (1%) hyperpolarized 5-HT neurons by 6.52 ± 3.94 mV and inhibited spontaneous firing. A subsequent decrease in pH from 7.4 to 7.2 depolarized neurons by 4.07 ± 2.10 mV, but that was insufficient to reach threshold for firing. Depolarizing current restored baseline firing and the firing frequency response to acidosis, indicating that isoflurane did not block the underlying mechanisms mediating chemosensitivity. These results demonstrate that isoflurane masks 5-HT neuron chemosensitivity in vitro and in situ and markedly decreases the HCVR in vivo. The use of this class of anesthetic has a particularly potent inhibitory effect on chemosensitivity of 5-HT neurons.